Development and Evaluation of an Interactive 360 Degree Video for Biomedical Instrumentation Course - Muhammad Syamil Rozmi; Marzita Hj Mansor (International Journal of Multimedia and Recent Innovation (IJMARI), 2023)
In the age of globalisation, the educational system has undergone digital transformations in tandem with technological advancements. This change has aided in the creativity of teaching and learning, which is no longer centred on using conventional ideas to aid in students' learning. For the majority of skills, especially engineering, practical experience is appropriately accompanied by theoretical knowledge as part of educational requirements. However, it has been impossible for students to acquire the necessary expertise due to expensive maintenance costs and restricted access to outside facilities. Due to the large number of studies concentrating on 360-degree video as a supporting solution, this project has taken the initiative to investigate the use of 360-degree video as a learning aid, recognising the importance of offering supporting solutions for student learning. As a result, the goal of this project is to develop and evaluate an interactive 360-degree video for the Biomedical Instrumentation course based on the ADDIE instructional model to aid in students' learning. In order to create instructional tools that achieve the optimal educational goal among diploma students of Electronics Engineering (Medical) in Sultan Salahuddin Abdul Aziz Shah Polytechnic, this study modified three learning models and used the ADDIE instructional model. 30 students took part in the evaluation phase by completing the System Usability Scale (SUS) questionnaire to rate the usability of the interactive 360-degree video. Based on the study's overall findings, the majority of students gave the developed interactive 360-degree video system good scores for usability, well-integrated features, and fast learning with the use of an interaction interface. Overall, the findings indicated that the development process of an interactive 360-degree video system was a success, and that it is easily integrated and usable as a digital educational tool for teaching and learning.